Notas sobre el che - Bertolotti, Virginia (2010)
In the present work, I review, in the first place, the bibliography that summarizes the discussion surrounding the etymology of the word che. Then, I analyze the uses of this term in the diachrony as in the synchrony of the Río de la Plata Spanish, which allows me to propose a classification of the uses of the word che in this region. In the third part of the article, I discuss the categorial adscrption of the word che. Finally, the categorial analysis of the diachronic and synchronic empirical evidence allows me to conclude that the vocative uses of the term are a loan from the nominal determinant of the guaraní language, and not a phonic change in the Spanish interjection, thus resolving the etymological issues.